Clinical profile of patients suffering from chest trauma who underwent chest drainage in the city of Belém-Pa, from 2015 to 2017 (Research, Society and Development, 2021)
Objective: To analyze the clinical profile of patients suffering from thoracic trauma treated at a private clinic affiliated with SUS in the city of Belém, in the State of Pará, Brazil. Method: Cross-sectional, retrospective, documentary study, with a quantitative approach carried out from 2015 to 2017. Data were collected with a time frame corresponding to the period from January 2015 to January 2017, totaling 3,700 cases. A sample error of 5% was adopted, with a 95% confidence level; establishing as sample n = 305 calls registered in the service database. Results: 83% were male and 28% female and the highest frequency in the age range was 20 to 34. Final considerations: Young men, in productive age, are the main ones affected by chest trauma, therefore it is of fundamental importance that everyone involved reflects on their behavior.